2014
DOI: 10.1155/2014/836375
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Fuel Consumption and Exhaust Pollutant Using Intelligent Transport Systems

Abstract: Greenhouse gas emitted by the transport sector around the world is a serious issue of concern. To minimize such emission the automobile engineers have been working relentlessly. Researchers have been trying hard to switch fossil fuel to alternative fuels and attempting to various driving strategies to make traffic flow smooth and to reduce traffic congestion and emission of greenhouse gas. Automobile emits a massive amount of pollutants such as Carbon Monoxide (CO), hydrocarbons (HC), carbon dioxide (CO2), par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…However, velocities between 16.7 m/s and 22. 2 m/s result in reduced fuel consumption and pollution [32]. Variations in velocity can be reduced with the regulation parameter b in autonomous vehicles to reduce fuel consumption and pollution.…”
Section: Resultsmentioning
confidence: 99%
“…However, velocities between 16.7 m/s and 22. 2 m/s result in reduced fuel consumption and pollution [32]. Variations in velocity can be reduced with the regulation parameter b in autonomous vehicles to reduce fuel consumption and pollution.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, green driver make headway without obstructing other drivers and maintain the safe distance to other vehicles without compromising traffic flow. Tang et al [73] have investigated the impact of traffic density to multiple headways from the perspective of fuel consumption. They found that at a 20-m initial headway, a lower car density (20 nos) results in 13.4 L/100 km fuel consumption compared to a higher car density (80 nos), which consumes 13.1 L/100 km under the influence of ramps.…”
Section: Literature Content Analysis and Synthesizementioning
confidence: 99%
“…Traffic signal coordination could promote traffic flow and reduced CO 2 and NO x emissions by 10%. Nasir et al [14] conducted vehicle exhaust pollutant emissions tests concerning HC, CO, CO 2 , particulate matter (PM) and NO x under traffic conditions of free-flow conditions, moderate congestion and severe congestion. ey indicated that the shortest path was not the path with the least emissions.…”
Section: Introductionmentioning
confidence: 99%
“…e quantitative evaluations regarding the overall effects of one-way traffic management on traffic network emissions are lacking. Moreover, microscopic emission models and traffic simulation tools are generally applied for traffic emission assessment [14], since it is o en not feasible to evaluate the environmental effects of traffic management measures based on the trial-and-error field experiments. However, the majority of studies using the microscopic traffic simulation with instantaneous emission models in the assessment, did not calibrate and examine the emission models based on the real world emission data that consider vehicle dynamics and di erent vehicle standards in di erent regions [21].…”
Section: Introductionmentioning
confidence: 99%